An Investigation of Corporate Approaches to Sustainability in the Construction Industry. (2017) - Afzal, Fatima; Lim, Benson; Prasad, Deo
Abstract: Corporate sustainability demands the integration of environmental performance, social justice and economic efficiency and, into company's operational practices. Construction companies are increasingly under pressure to commit to and report on the overall sustainability performances of operational initiatives. The aim of this paper is to investigate the sustainability performance of the top 50 construction contractors listed by Engineering News Record (ENR) against the triple bottom line. Under this aim, the specific objectives are: (i) examine the approaches adopted by construction firms to disclose their commitments to sustainability; (ii) review the firms' annual and sustainability reports; and (iii) analyse the sustainability performance of construction firms against the GRI (Global Reporting Initiatives) guidelines. This study adopted survey design in which data were collected by reviewing publicly available organisational documents. Afterward, content analysis was conducted. The results indicate that financial performance is still the main target of most organisations. European contractors are considered best and Australasian contractors on the other side are considered as worst in reporting sustainability initiatives.